Comparing Routine HIV and Hepatitis C Virus Screening to Estimate the Effect of Required Consent on HIV Screening Rates Among Hospitalized Patients. (January 2022) - Felsen, Uriel R.; Tlamsa, Aileen; Moir, Lorlette; Shukla, Shuchin; Thompson, Devin; Weiss, Jeffrey M.; Heo, Moonseong; Litwin, Alain H.
Objectives: Routine screening for HIV and hepatitis C virus (HCV) among specified age cohorts is recommended. New York State requires consent before screening for HIV but not HCV. We sought to estimate the effect of the consent requirement on screening rates for HIV. Methods: We performed a retrospective study of patients hospitalized in 2015-2016 at a tertiary care hospital in the Bronx, New York, during a period when prompts in the electronic health record facilitated screening for HIV and HCV among specified age cohorts. We compared proportions of patients eligible for screening for HIV and/or HCV who underwent screening and used generalized estimating equations and a meta-analytic weighted average to estimate an adjusted risk difference between undergoing HIV screening and undergoing HCV screening. Results: Among 11 938 hospitalized patients eligible for HIV and/or HCV screening, 38.5% underwent screening for HIV and 59.1% underwent screening for HCV. The difference in screening rates persisted after adjusting for patient and admission characteristics (adjusted risk difference = 22.0%; 95% CI, 20.6%-23.4%). Conclusions: Whereas the requirement for consent was the only difference in the processes of screening for HIV compared with screening for HCV, differences in how the 2 viruses are perceived may also have contributed to the difference in screening rates. Nevertheless, our findings suggest that requiring consent continues to impede progress toward the public health goal of routine HIV screening.